Matrix Metalloproteinases 7 and 10 Are Prognostic Biomarkers for Systemic Cardiovascular Risk in Individuals with Peripheral Artery Disease - Ben Li; Farah Shaikh; Houssam Younes; Batool Abuhalimeh; Abdelrahman Zamzam; Rawand Abdin; Mohammad Qadura (Biomolecules, 2025)
Background/Objectives: Peripheral artery disease (PAD) is associated with an increased risk of major adverse cardiovascular events (MACE), such as myocardial infarction and stroke, which are the top mortality causes in the PAD population. However, the identification of reliable biomarkers for predicting MACE in PAD patients remains limited. Proteins involved in extracellular matrix (ECM) remodeling have been implicated in atherosclerosis and may serve as potential indicators of cardiovascular risk. This study aimed to evaluate a panel of circulating proteins involved in ECM remodeling to identify those predictive of 2-year MACE in individuals with PAD. Methods: A prospective cohort of 465 PAD patients was enrolled and followed for 24 months. At baseline, plasma levels of nine ECM-related proteins were quantified. The outcome of interest was a 2-year MACE, defined as a composite of myocardial infarction, stroke, or mortality. Protein level differences between MACE vs. non-MACE patients were analyzed using Mann–Whitney U tests. Cox proportional hazards models, adjusted for baseline variables (including known cerebrovascular and coronary disease), were used to determine the independent associations between each protein and 2-year MACE. Subgroup analyses were conducted for diabetic and female patients, who are known to be at high risk for adverse events. Results: The mean age of the participants was 71 (SD 10) years, with 31.1% identifying as female and 47.2% having diabetes. Over two years, 84 patients (18.1%) experienced MACE. Among the proteins analyzed, matrix metalloproteinase-10 (MMP-10) and matrix metalloproteinase-7 (MMP-7) were significantly elevated in those who developed MACE compared to those who did not: MMP-10 (710.60 pg/mL [SD 46.09] vs. 672.40 pg/mL [SD 45.04], p = 0.032) and MMP-7 (5.20 pg/mL [SD 4.11] vs. 4.76 pg/mL [SD 3.86], p = 0.048). Both independently correlated with 2-year MACE after adjustment for all baseline factors: MMP-10 (HR 1.32, 95% CI 1.16–1.51, p = 0.023) and MMP-7 (HR 1.17, 95% CI 1.05–2.68, p = 0.026). Subgroup analyses revealed that MMP-10 was associated with MACE in diabetic patients (HR 1.18, 95% CI 1.13–1.53, p = 0.019), while MMP-7 was associated with MACE among females (HR 1.31, 95% CI 1.15–1.69, p = 0.009). Conclusions: MMP-10 and MMP-7 emerged as independent biomarkers for prognosticating 2-year MACE in PAD patients, suggesting their utility in systemic cardiovascular risk stratification. Measuring these proteins could enhance clinical decision-making by identifying high-risk individuals with PAD who may benefit from multidisciplinary vascular evaluation and intensified treatment strategies, ultimately aiming to reduce cardiovascular complications in the PAD population.